Training Compost from Environmentally Friendly Rice Husk Ash Waste in Puyung Village - sri puji astuti; rina kurnianingsih (Yogyakarta State University, 2019)
Community service activities has been done with target audiences of tofu tempe craftsmen, farm laborers, and housewife in Lingkung Daye Hamlet, Puyung Village, Jonggat Sub-district. The purpose of this activity were to socialize the importance of the clean environment to the residents of Lingkung Daye Hamlet, to socialize the benefit of rice husk ash to make solid compost with the windraw method, to provide solutions the benefit of compost and marketing prospects. The method applied in this PPM activity were lectured, discussion, question and answer by applying the Applied Group Discuss (AGD) technique involving the community, demonstrations, practices and survey the location of the demonstration plot for the application of compost fertilizer that had been made previously on the agricultural land of tomatoes and chillies. An evaluation was conducted by monitor the success of the activity, using the observation method. The conclusion were 100% of participants understood the material presented, as many as 90% of participants understood how to make solid compost from rice husk ash and as many as 100% of motivated participants looked for alternatives to processing husk ash waste and as many as 80% of participants were motivated to apply and sold the solid compost products.